Pathogenic and genetic diversity among Indian isolates of Scierospora graminicoia from pearl millet - SEETHA KANNAN and V.P. RAO, S. SIVARAMAKRISHNAN, R.P. THAKUR (Indian Phytopathology, 2003)
Pathogenic and genetic diversities among 15 isolates of Sclerospora graminico/a, the pearl millet downy mildew pathogen, collected from various pearl millet cultivars in India were assessed. Pathogenic variability was assessed by their disease causing potential on 12 pearl millet differential lines in a greenhouse experiment. The dendrogram based on mean disease incidence data classified the 15 isolates into five major virulence groups. Genetic diversity was assessed using amplified fragment length polymorphism (AFLP). Of the 12 primer combinations used in AFLP, five gave highly polyrnorphlc patterns. The dendrogram of the AFLP marker data classified the 15 isolates into five major genetic clusters. Results indicated hostdirected virulence selection and genetic changes in some isolates that were maintained on alternative host for multiple asexual generations.